A one pot, metal-free, three-component domino sequence for the synthesis of furans: an efficient C–O and C–N bond formation approach. Issue 46 (20th April 2016) - Guo, Pengfeng; Wang, Changcheng; Chen, Ya; Ou, Caijun; Jiang, Hangqi; Chen, Weifeng; Chen, Weixin; Cao, Hua
Abstract : A novel one pot, metal-free, three-component domino reaction for the formation of furan derivatives has been developed from 3-phenylpropiolaldehyde, 1, 3-dicarbonyl compounds and aromatic amine or aliphatic acid. Abstract : A novel one pot, metal-free, three-component domino reaction for the formation of furan derivatives has been developed from 3-phenylpropiolaldehyde, 1, 3-dicarbonyl compounds and aromatic amine or aliphatic acid. This transformation provided a general and facile access to the construction of C–O and C–N bonds to prepare various bioactive furans in good yields.